Declining land use mix: are residential areas of Iskandar Malaysia promoting low carbon travel? - Majid, M. Rafee (2015)
Diversity in the context of land use planning refers to the variety of uses for land; and the success of diversity can be achieved through mixed use development. Although mixed land uses are popularly practised in mixed use development for the past decades, current land use practices have moved towards the separation of residential and non-residential land uses. Observing this changes in land use trend, this paper discusses the changes in mixed land use from 1980s to 2000s in Iskandar Malaysia, Johor. The study is aimed at determining the level of land use diversity and its trend within the past few decades by using diversity indices of Simpsons Diversity Index (SDI) and Shannons Diversity Index (ShaDI). It has been hypothesised that land use diversity indices have been steadily on the decrease but quickened beyond 2005. According to Harris (2000), mixed uses not only increase the density but also gives choices through diversity of land uses. It is also supported by Aurand (2010) who observed that mixed use development means the combination of commercial, residential and industrial uses within one geographical area and not separating of residential and non-residential land uses.